Changes in Cardiovascular Health during Young Adulthood and Subclinical Atherosclerosis in Middle Age: The CARDIA Study. Issue 1 (17th March 2023) - Ye, Xiaomin; Xiong, Zhenyu; Li, Jiaying; Lin, Yifen; Xie, Peihan; Zhong, Xiangbin; Huang, Rihua; Zhuang, Xiaodong; Liao, Xinxue
Background and aims: The benefits of reaching ideal cardiovascular health (CVH) are well known, but it is unclear whether positive CVH changes from young adulthood to middle age reduce subclinical atherosclerosis risk. This study examined associations of changes in CVH from young adulthood to middle age and CVH in young adulthood with subclinical atherosclerosis. Methods: Data was analyzed from the Coronary Artery Risk Development in Young Adults (CARDIA) study. CVH was examined at years 0 and 20 using Life Simple 7 metrics from AHA guideline. Coronary artery calcium (CAC) was identified at years 20 and 25. Carotid intima-media thickness (IMT) was identified at year 20. Results: Among 2, 935 participants (56.2% women, 46.7% black), the change of CVH score was –1.26 (2.13). For per 1-unit increase in CVH at baseline, the adjusted odds ratios (ORs) of presence of CAC and IMT were 0.81 (95% CI 0.78, 0.86) and 0.85 (95% CI 0.76, 0.94), respectively. For per 1-unit increase in CVH changes, the adjusted ORs of CAC and IMT were 0.86 (95% CI 0.82, 0.90) and 0.81 (95% CI 0.73, 0.90). Compared with stable moderate CVH, improvement from moderate to high was associated with a lower risk of CAC (0.64 [95% CI 0.43, 0.96]), while retrogression from moderate to low was associated with a higher risk of CAC (1.45 [95% CI 1.19, 1.76]). Conclusions: Positive changes of CVH during young adulthood are associated with negative subclinical atherosclerosis risk in middle age, indicating the importance of reaching an ideal cardiovascular health status through young adulthood.